An Unpublished Poem by Mehmed Rešid (Prilozi za orijentalnu filologiju, 2017)
Mehmed- Rešid belongs to that large number of our poets who wrote in Oriental languages and about whose lives there is very little information. Although we cannot say much about the life of this poet, we can conclude on the basis of his poems that he was born in Sarajevo at the middle of the 17th century. The date of his death is not known.He wrote a divan (collection of poems) from which we have here singled out one poem about transience of life and inconstancy of fate. The occasion for such thoughts the poet found in tragic events in Bosnia during the incursion of Eugene of Savoy in 1697. In his verse Mehmed Rešid showed himself to be a very good connoisseur of Arabic poetry, especially its metrics. His verses are not artificial, they have retained their beauty showing at the same time Mehmed Rešid's great capability and wide range of poetic expression.